Assessing the outcomes of participatory research: protocol for identifying, selecting, appraising and synthesizing the literature for realist review - Greenhalgh Trish; Wong Geoff; Seller Robbyn; Bush Paula L; Sirett Erin; Henderson Jim; Salsberg Jon; Macaulay Ann C; Pluye Pierre; Jagosh Justin; Cargo Margaret; Herbert Carol P; et al. (Implementation Science, 2011)
Abstract Background Participatory Research (PR) entails the co-governance of research by academic researchers and end-users. End-users are those who are affected by issues under study (e.g., community groups or populations affected by illness), or those positioned to act on the knowledge generated by research (e.g., clinicians, community leaders, health managers, patients, and policy makers). Systematic reviews assessing the generalizable benefits of PR must address: the diversity of research topics, methods, and intervention designs that involve a PR approach; varying degrees of end-user involvement in research co-governance, both within and between projects; and the complexity of outcomes arising from long-term partnerships. Methods We addressed the above mentioned challenges by adapting realist review methodology to PR assessment, specifically by developing inductively-driven identification, selection, appraisal, and synthesis procedures. This approach allowed us to address the non-uniformity and complexity of the PR literature. Each stage of the review involved two independent reviewers and followed a reproducible, systematic coding and retention procedure. Retained studies were completed participatory health interventions, demonstrated high levels of participation by non-academic stakeholders (i.e., excluding studies in which end-users were not involved in co-governing throughout the stages of research) and contained detailed descriptions of the participatory process and context. Retained sets are being mapped and analyzed using realist review methods. Results The librarian-guided search string yielded 7,167 citations. A total of 594 citations were retained after the identification process. Eighty-three papers remained after selection. Principle Investigators (PIs) were contacted to solicit all companion papers. Twenty-three sets of papers (23 PR studies), comprising 276 publications, passed appraisal and are being synthesized using realist review methods. Discussion The systematic and stage-based procedure addressed challenges to PR assessment and generated our robust understanding of complex and heterogeneous PR practices. To date, realist reviews have focussed on evaluations of relatively uniform interventions. In contrast our PR search yielded a wide diversity of partnerships and research topics. We therefore developed tools to achieve conceptual clarity on the PR field, as a beneficial precursor to our theoretically-driven synthesis using realist methods. Findings from the ongoing review will be provided in forthcoming publications.